Differentiating between gifts and bribes from Muslims’ perspective: an empirical study of auditors ethics in Saudi Arabia - Al-Hasan Al-Aidaros (Future Business Journal)
Abstract The objective of this study is to find out the underlying structure of the auditors’ ethics of workplace gifts, as well as to explore differences between gifts and bribes, in a Muslim Arab country, that is Saudi Arabia. By developing a new questionnaire specifically for this study, the paper adopted a quantitative methodology using interdependency analysis, i.e., Exploratory Factor Analysis (EFA) that was confirmed through convergent and discriminant validity. The data were collected from 268 accountants and faculty members who are experts in accounting and finance, from government and private sectors in Saudi Arabia. The results showed that the underlying ethical structure consists of ten main components. These components include rules covering different aspects, (1) professional ethics on gift refusal, (2) Islamic ethical perspective on gift-giving, (3) subtle gift influence on independence, (4) financial boundaries and ethical client relations, (5) contextual and cultural justifications for gift acceptance, (6) post-audit gift ethics, (7) client dependency and compromised independence, (8) reputation risk from high-value gifts, (9) deterrence through penalties and professional conduct, and (10) regulatory oversight and gift governance. Moreover, the results show the main differences between gifts and bribes from the perspective of Muslims. This study adds to the ethical literature for auditor’s dealings with gifts in Muslim-majority countries with special focus on Saudi Arabia, a country with unique cultural and tribal characteristics. It covers both theoretical and empirical aspects of the issue. This study serves decision makers in the field of accounting and auditing. Relevant governmental and professional bodies in Saudi Arabia may benefit from this study to develop legal policies and regulations to determine the ethical rules that accountants and auditors must follow when receiving or giving workplace gifts.